Syn-gas from waste: the reduction of CO2 with H2S. Issue 4 (21st February 2019) - Alderman, Nicholas P.; Peneau, Virginie; Viasus, Camilo J.; Korobkov, Ilia; Vidjayacoumar, Balamurugan; Albahily, Khalid; Gambarotta, Sandro
Abstract : In this paper, we demonstrate that syngas (H2 /CO) can be produced from oil waste (H2 S/CO2 ) forming SO2 and S as secondary products at 600–800 °C in a flow reactor set-up. Abstract : In this paper, we demonstrate that syngas (H2 /CO) can be produced from oil waste (H2 S/CO2 ) forming SO2 and S as secondary products at 600–800 °C in a flow reactor set-up. Numerous different metal sulfide catalysts have been tested for activity, with FeS and NiS appearing to be the most active. In both cases, the catalyst remains active after 120 hours online. X-ray diffraction confirmed that the catalyst remains under the form of the metal sulfide.